PERAN TATA KELOLA PERUSAHAAN PADA PENGARUH PENGUNGKAPAN SISTEM PENGENDALIAN INTERNAL TERHADAP KINERJA PERUSAHAAN KESEHATAN - Weli Weli; Yostian Hadinata; Tiffany Tiffany; Victoria Bella; Natasha Vania Devi (Jurnal Bisnis dan Akuntansi, 2023)
The purpose of this study was to analyze the effect of the internal control system disclosure on the performance of companies with corporate governance as measured by the proportion of independent commissioners as a moderating variable. Data analysis using descriptive analysis method and hypothesis testing with path analysis using PROCESS and SPSS. The research population is the annual report of health sector companies that have been listed on the Indonesia Stock Exchange from 2018-2021. The sample used was 62 company reports which were collected by purposive sampling method. The results of the data analysis found that the internal control disclosure variable had a significant effect on company performance and the corporate governance variable moderated the relationship between internal control disclosures and company performance.